The standards of an ultrasound examination of the prostate gland. Part 1 - Janusz F. Tyloch; Andrzej Paweł Wieczorek (Journal of Ultrasonography, 2016)
The article discusses the principles of the proper performance of the ultrasound examination of the prostate gland. The paper has been divided into two parts: the general one and the detailed one. The first part presents the necessary requirements referring to the ultrasound apparatus for performing transabdominal examinations of the urinary bladder and the prostate gland as well as for transrectal examinations of the prostate gland. The paper also describes the techniques of performing both examinations together with the methods of measuring the capacity of the urinary bladder and the volume of the prostate gland. It also mentions the most frequent indications for performing the examinations as well as diagnostic algorithms applied in case of finding irregularities. The transabdominal ultrasonography is a part of the examination of the abdominal organs and it should be performed in patients complaining of dysuric symptoms. An addition to the examination, especially when the prostate gland is enlarged, should be the measurement of the capacity of the urinary bladder and the assessment of the amount of residual urine after voiding. The indications for the endosonographic examination of the prostate gland are patological changes found in the per rectum examination, elevated concentration of the prostate-specific antigen in the blood serum, cancer and inflammations of the prostate gland if an abscess is suspected, qualification for surgery in the course of benign prostatic hyperplasia and the diagnostics of disorders of ejaculation. A standard procedure performed in case of prostate cancer for the purpose of obtaining specimens for the histopathology examination is biopsy carried out with transrectal ultrasound imaging. The paper presents the indications and techniques of performing prostate biopsy, as well as the types of biopsies together with the necessary preparation and the protection against its side effects for the patient. The paper also lists the necessary elements of the description of the presented procedures. The second part of the paper presents the application of the ultrasound examinat.